Education Quality Improvement in the Management Institute through Six Sigma Approach - Sen, A. K.; Sanchis, E. J. (SFIMAR Research Review, 2012)
In the present competitive world, the institutions offering management education will survive only when they will adopt different Quality Improvement (QI) strategies. Most of the institutions in India and world over have adopted successfully quality improvement (QI) strategies like ISO 9000, Total Quality Management (TQM), Benchmarking and Business Process Reengineering (BPR). Recently six-sigma strategy has been successfully adopted by industries and business world over for quality improvement. Six-sigma is basically a business strategy and systematic methodology, use of which leads to breakthrough in profitability through quantum gains in service quality and customer satisfaction. In the light of the above, this work presents an investigation in the implementation of six-sigma approach for improving the quality of the management education in India. To increase number of successful graduates from the institutes, the role of six-sigma members such as executive leaders, champions, master black belts and green belts are introduced. The functions of each member are defined and implemented according to the sixsigma life cycle. The investigation is centered on the detailed study for improving the student result in the university examination, which is one of the important indicators of quality education. In this competitive, globalised wireless world any institute can grow only when they will continuously evaluate their products - the student and the process of making them marketable. So a study of the process of making the quality product has been taken up using Quality Function Deployment (QFD) chart. The existing product and process or designing new product or process requires a lot of time. So, QFD software has been used for this purpose. The software supports the graphical output of customer competitive evaluation and technical competitive evaluation in addition to providing the demanded weights for the customers’ requirements and functional weights for the technical requirements or control parameters. It also provides an indication for the major requirements/ demands of the process improvements. The six-sigma approach has increased the sigma level significantly. The results are encouraging and the six-sigma approach leads to a successful methodology in encouraging the number of successful candidates with improved quality in management education.